Constructing Interreligious Dialogue through Local Wisdom for Peacebuilding in Nggeru Kopa Hamlet, Indonesia - Jamaludin Jamal; Nurul Yaqinah; Abdul Malik (Jurnal Dialog, 2026)
Religious multiculturalism presents both opportunities for harmony and risks of conflict when differences are exploited, with ineffective communication frequently triggering social disintegration. In this context, religious leaders play a pivotal role in bridging societal divides and cultivating shared understanding to strengthen interfaith relations while countering religious radicalism. This study employs qualitative methods with a phenomenological approach, collecting data through observation, interviews, and documentation, analyzed via data reduction, presentation, and verification techniques. Results demonstrate that religious leaders in Nggeru Kopa Hamlet drive peacebuilding by constructing social values anchored in local traditions:such as the InaRiha practices in prayer gatherings, second,consensus prohibiting open pork processing by Christians to respect Muslim neighbors, and  mutual cooperation in Mbolo Weki and Karawi Ulucempe traditions. These mechanisms fortify interfaith bonds and ensure social stability amid diversity.These practices strengthen interfaith relations and ensure social stability amidst diversity. These findings contribute to interfaith communication theory by demonstrating how religious leaders act as social architects, not merely facilitators, of peace in a multicultural society.   .